Identification of sea snake meat adulteration in meat products using PCR-RFLP of mitochondrial DNA - Sunutcha Suntrarachun; Lawan Chanhome; Montri Sumontha (Food Science and Human Wellness)
PCR-RFLP based technique for identification of sea snakes in Thai waters was achieved by developing species-specific markers. To distinguish between sea snake species, the PCR products of cytochrome b (Cyt b), 12S and 16S rRNA were sequenced and cut with different restriction endonuclease, Alu I and Hinf I. Each enzyme generated different - sized fragments which specific to Cyt b of eight sea snake species. However, the identical pattern was found among Hydrophis group. This result could be resolved by using these enzymes 12S rRNA digestion. This technique was successfully applied to blood, shed skin, raw meat, cooked meat, sea snake-fish binary admixture, and sea snake-pork binary admixture. Hence, it could be applied for identification when sea snake meat adulteration in meat products and sold as meatballs to reduce production costs. Hopefully, this technique would improve sea snake species identification when morphological examination is no longer possible because the animals are already processed. This is very important to track when sea snake species are being hunted and also used to assess the conservation and management of the sea snakes in Thai waters, especially the Gulf of Thailand. Keywords: Sea snakes, PCR-RFLP, Adulteration